Study of Saponin Components after Biotransformation of Dioscorea nipponica by Endophytic Fungi C39. (11th May 2022) - Huang, Nannan; Yu, Dan; Huo, Jinhai; Wu, Junkai; Chen, Yiyang; Du, Xiaowei; Wang, Xijun
Abstract : This study conducted the solid fermentation process of Dioscorea nipponica using endophytic fungi C39 to determine the changes in the diosgenin concentration. The results revealed that endophytic fungi C39 could effectively biotransform the saponin components in D. nipponica . Moreover, the maximum increase in the diosgenin concentration reached 62.67% in 15 days of solid fermentation. MTT assay results demonstrated that the inhibitory effects of the fermentation drugs on four types of cancer cells (liver cancer cells (HepG2), stomach cancer cells (BGC823), cervical cancer cells (HeLa), and lung cancer cells (A549)) were better than those of the crude drugs obtained from D. nipponica . The chemical composition of the samples obtained before and after the biotransformation of D. nipponica was analyzed by UPLC-Q-TOF-MS. A total of 32 compounds were identified, 21 of which have been reported in Dioscorea saponins and the ChemSpider database and 11 compounds were identified for the first time in D. nipponica . The biotransformation process was inferred based on the variation trend of saponins, which included transformation pathways pertaining to glycolytic metabolism, ring closure reaction, dehydrogenation, and carbonylation. The cumulative findings provide the basis for the rapid qualitative analysis of the saponin components of D. nipponica before and after biotransformation. The 11 metabolites obtained from biotransformation are potential active ingredients obtained from D. nipponica, which can be used to further identify pharmacodynamically active substances.